Exploring the Impact of Inquisitiveness on Technology Adoption and Creativity on Work Efficiency: Insights from the Fashion Creative Industry in Bandung, Indonesia - Sidharta, Iwan; Suherman, Asep Rochyadi; Herawati, Octaviane; Astuti, Riska Yuni; Andyandi, Pebrio Tri (Jurnal Computech & Bisnis (e-journal), 2024)
Technology plays a vital role in addressing key challenges in the fashion industry, including high personalization, environmental sustainability, and increased productivity. The aim of this study is to explore the impact of technological advancements on innovation in the fashion industry, particularly among SMEs in Indonesia. Additionally, this research will investigate Curiosity, technology readiness, creativity, and employee performance enhancement in the creative fashion industry. This research employs a survey approach in the creative fashion industry sector in Bandung City. Respondents consist of employees with a minimum of 1 year of experience in fashion companies in Bandung City, selected through simple random sampling. Out of 322 respondents, data is tested for the proposed research model. The validity and reliability of the instruments will be tested for the first-order and second-order models. Structural analysis and Structural Equation Modeling are utilized to generate a valid research model prediction. The findings confirm that Curiosity significantly influences technology readiness and creativity in the Bandung fashion industry. The intrinsic drive to seek additional information stimulates innovation and employee performance. Individuals with a strong sense of curiosity tend to be more prepared to embrace technology, enhance creativity, and demonstrate superior task performance.  The  profound impact of  Curiosity on  Technology  Readiness  and  Creativity towards task performance demonstrates a complex aspect of originality. Employee performance, involving behavior and actions in task completion, is closely linked to these factors. Curiosity encourages exploration of new technologies, innovative thinking, and creative approaches to tasks. Employees who exhibit curiosity, technology readiness, and creativity tend to excel in their work, bringing new perspectives, innovative solutions, and high engagement in the Bandung fashion industry. The limitations of this study include the need for further research to explore the long-term effects of Curiosity, technology readiness, and creativity on task performance. Future studies could investigate the role of other factors such as organizational support and individual motivation in shaping employee performance in the creative fashion industry. Subsequent research could deepen the understanding of specific industry contexts, delve further into leadership, or explore the intersection of individual and organizational factors on performance outcomes.